Hyperintensionality, Identity and Excluded Middle - Chlebowski, Szymon (Logic and Logical Philosophy, 2025)
We introduce new semantics for the intuitionistic variant of the weakest non-Fregean logic, SCI. This semantics captures the notion of identity within a constructive framework and aligns with our intuitive understanding of it, which is provided by the Brouwer-Heyting–Kolmogorov interpretation. Moreover, we demonstrate how this approach naturally leads to interesting extensions of ISCI.